Measurement and Quantification of Gross Human Shoulder Motion - Jeremy T. Newkirk; Martin Tomšič; Charles R. Crowell; Michael A. Villano; Michael M. Stanišić (Applied Bionics and Biomechanics)
The shoulder girdle plays an important role in the large pointing workspace that humans enjoy. The goal of this work was to characterize the human shoulder girdle motion in relation to the arm. The overall motion of the human shoulder girdle was characterized based on motion studies completed on test subjects during voluntary (natural/unforced) motion. The collected data from the experiments were used to develop surface fit equations that represent the position and orientation of the glenohumeral joint for a given humeral pointing direction. These equations completely quantify gross human shoulder girdle motion relative to the humerus. The equations are presented along with goodness-of-fit results that indicate the equations well approximate the motion of the human glenohumeral joint. This is the first time the motion has been quantified for the entire workspace, and the equations provide a reference against which to compare future work.